Scientific publication speed and retractions of COVID-19 pandemic original articles - Luisa Schonhaut; Italo Costa-Roldan; Ilan Oppenheimer; Vicente Pizarro; Dareen Han; Franco Díaz (Pan American Health Organization, 2022)
Objective. To describe the editorial processing time of published COVID-19 research articles and compare this with a similar topic, human influenza, and analyze the number of publications, withdrawals, and retractions. Methods. A descriptive-analytical study using PubMed on research articles with the MeSH terms human influenza and COVID-19. Time to acceptance (from submission to acceptance) and time to publication (from acceptance to publication) were compared. Retractions and withdrawals were reviewed both qualitatively and quantitatively. Results. There were 31 319 research articles on COVID-19 and 4 287 on human influenza published during 2020. The median time to acceptance for COVID-19 was lower than that for human influenza (8 vs. 92 days). The median time to publication for COVID-19 articles was shorter than those on human influenza (12 vs. 16 days); 47.0% of COVID-19 research articles were accepted within the first week of submission, and 19.5% within one day. There were 82 retractions and withdrawals for COVID-19 articles, 1 for human influenza, and 5 for articles that contain both terms; these were mainly related to ethical misconduct, and 27 (31.0%) were published by the same group of authors in one highest-quartile journal. Conclusions. The conundrum between fast publishing and adequate standards is shown in this analysis of COVID-19 research articles. The speed of acceptance for COVID-19 manuscripts was 11.5 times faster than for human influenza. The high number of acceptances within a day or week of submission and the number of retractions and withdrawals of COVID-19 papers might be a warning sign about the possible lack of a quality control process in scientific publishing and the peer review process.